Bifidobacterium longum subsp. infantis Shifts Global Transcriptional and Post-translational Modification Signals in Preterm Infant Gut Epithelial Cells. (14th June 2022) - Bolino, Matthew; Leff, Abigail; Ferguson, Bradley; Frese, Steven
Abstract: Objectives: Bifidobacterium longum subsp. infantis (B. infantis) is an important human infant gut symbiont that confers benefits to the infant by shaping the gut microbiome in vivo . Here, we investigated the transcriptomic and post-translational modification (PTM) impacts of B. infantis on host gut epithelial cells representative of preterm infants, in vitro . Methods: RNA isolated from preterm infant intestinal epithelial cells (HIEC-6) exposed to sterile, cell-free B. infantis supernatants or controls (no supernatant) for 20 hours was subjected to RNA-sequencing to assess global transcriptional changes (n = 6/group). Using the same approach, HIEC-6 cells were incubated for 3 or 20 hours, with or without supernatant (10% v/v; n = 3/group), before harvest for cellular proteins and subsequent western blotting. Gels were probed for α-tubulin, acetylated α-tubulin, Extracellular signal-Regulated Kinase (ERK), and phosphorylated ERK as markers of PTM activity. Results: Global transcriptomic profiles were significantly different between cells exposed to supernatant and those that were not (P = 0.006) and gene pathways involved in anti-inflammatory responses and chemotaxis were significantly upregulated (P < 0.01). Western blotting revealed significant increases in acetyl-α-tubulin and phospho-ERK in cells exposed to supernatant relative to the control group (P < 0.05), while total α-tubulin and ERK concentrations were not significantly different (P > 0.05). Conclusions: These findings demonstrate the ability of B. infantis to alter global transcriptional and PTM responses affecting inflammation, intracellular trafficking of α-tubulin, and transcription factor recruitment by ERK phosphorylation. These pathways regulate key cellular processes such as cell proliferation, differentiation, adhesion, migration and survival, providing molecular insights into the ability of B. infantis to regulate transcriptional and PTM processes in vitro . Funding Sources: This work was funded by the Department of Nutrition, the College of Agriculture, Biotechnology, & Natural Resources, the Nevada Agricultural Experiment Station, and the Vice President for Research and Innovation, as well as the NICHD, R03HD105881, and grants from the NIGMS (GM103440 and GM104944) from the NIH.